2024
DOI: 10.1007/s10787-024-01439-6
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine promotes ferroptosis through AKT-ERK1/2 and P53-SLC7A11 in rheumatoid arthritis

Chenyu Zhao,
Yunyuan Yu,
Guangrong Yin
et al.

Abstract: Objective Ferroptosis has been reported to play a role in rheumatoid arthritis (RA). Sulfasalazine, a common clinical treatment for ankylosing spondylitis, also exerts pathological influence on the progression of rheumatoid arthritis including the induced ferroptosis of fibroblast-like synoviocytes (FLSs), which result in the perturbated downstream signaling and the development of RA. The aim of this study was to investigate the underlying mechanism so as to provide novel insight for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 53 The p53 can transcriptionally repress SLC7A11 expression at the transcriptional level, thereby promoting the occurrence of ferroptosis in cells. 54 Also, p53 releases Arachidonate 12-lipoxygenase (ALOX12). Free ALOX12 oxidizes cell membrane phospholipids’ polyunsaturated fatty acid chains, leading to ferroptosis.…”
Section: Ferroptosis Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 The p53 can transcriptionally repress SLC7A11 expression at the transcriptional level, thereby promoting the occurrence of ferroptosis in cells. 54 Also, p53 releases Arachidonate 12-lipoxygenase (ALOX12). Free ALOX12 oxidizes cell membrane phospholipids’ polyunsaturated fatty acid chains, leading to ferroptosis.…”
Section: Ferroptosis Mechanismmentioning
confidence: 99%
“… 156 It is a potent inhibitor of system Xc − that characteristically inhibits cystine transport mediated by SLC7A11. 54 SAS can effectively induce ferroptosis in tumor cells such as Multiple myeloma (MM) cells, 157 Esophageal cancer (EC) cells 63 and TNBC cells. 158 Sorafenib is a protein kinase inhibitor approved for the treatment of hepatocellular carcinoma and advanced renal cell carcinoma.…”
Section: Ferroptosis Inducersmentioning
confidence: 99%
“…Additionally, the active peptide G1dP3 promotes RA-FLS ferroptosis through a p53/SLC7A11 axis-dependent mechanism ( 53 ). Sulfasalazine, an important biological agent, was found to inhibit System Xc- ( 54 ). Beyond the classical ferroptosis antioxidant pathways, the CoQ10 pathway, which is unrelated to GPX4, was found to act as a ROS scavenger and anti-inflammatory substance.…”
Section: Ferroptosis In Ramentioning
confidence: 99%
“…Studies have shown that ferroptosis in intestinal epithelial cells is involved in the pathophysiological mechanism of intestinal I/R injury 8 , 9 . In addition, some studies have found that SAS not only inhibits the NF-κB pathway, but also inhibits the ferroptosis signal pathway System Xc — 10 , 11 . The aim of this study was to evaluate the role of ferroptosis in perioperative LT intestinal injury in rats and further clarify the possible mechanism of the ferroptosis activator sulfasalazine (SAS) in perioperative LT-induced intestinal injury in rats.…”
Section: Introductionmentioning
confidence: 99%